Julio De Zan interpreter of Hegel - Lopez, Diana María (ARFIL y UNL, 2021)
In the tradition of philosophy in Argentina, Hegel has meant to this day a source of important views on the nature of society and history. The Phenomenology of the spirit turns out to be a provocation of the thought that finds in Julio De Zan (1940-2017) a privileged interpreter. From his academic beginnings as a professor and researcher, he was initially interested in this work. In the context of this dossier dedicated to “Hegel’s philosophy in Argentina”, we propose an analysis of two articles by Julio De Zan published at different times: “Sense and validity of the Phenomenology of the spirit” (1970) and “Experience and praxis. Method questions in Hegel’s Phenomenology of the Spirit” (2007).